A visão bernardina do índio n'O Ermitão do Muquém - Lima, Poliana Gonçalves (2009)
Bernardo Guimarães launches in 1858 the novel O ermitão do Muquém, which opens the sertanismo in our literature. In this study we analyze how this novel introduces the figure of the inlander in our literature to the detriment of the Indian figure, which until the period was the person elected to represent the nationality of our literature. We looked for since the early days of indianism in Brazil, with the historian Ferdinand Denis, passing for Indian authorities as Goncalves Dias, Gonçalves de Magalhães and José de Alencar, which nailed in his writings the figure of the Indian as a symbol of our national literature. We identified in what way that "good savage" was designed and built in the most vivid expression of the Brazilian literature in fact. Another aspect also analyzed is the regionalism in Brazil, as well as their representatives, as Afonso Arinos, Visconde de Taunay and own Bernardo Guimarães, which presents, although in different ways, the figure of the inlander of Brazil. In the novel O ermitão do Muquém, we analyze the Bernardina deconstruction of the Indian; as much in the characterization of the personages as of the proper spaces where they are inserted. We saw in this novel, as the figure of the crude and violent inlander, not finding the change of character in the indigenous culture, discover the redemption of the character in the religious mysticism of white space.Are displayed the three spaces:the space of "white" man in the raw wilderness, the Indian space with false idealization and, finally, the space of the white man of the converted man. The theoretical basis taken as supporting the analyses was the theory on the horizon of expectations of Hans Robert Jauss and the concept of discursive formation of Michel Foucault, in addition to narrative theories on the focus narrative, the spaces and other elements composers of narrative art.